Case Method Learning Method in Implementing Pancasila Values - Bella, Sinta; Nadeak, Desri Rut Hartati; Rasuna, Muhammad Ardiansyah; Simamora, Chintia Margaretha (Holistic Science, 2024)
This research aims to determine the implementation of Pancasila values ??through the application of case method-based learning methods in Civics subjects. PPKn learning is closely related to Pancasila, as well as the meaning contained in it will be useful for forming national character so that it is not eroded by the times. The type of research used is field research with a descriptive approach. The research subjects were 32 MTSs Nurul Amaliyah students. The results of the research show that the implementation and instilling of Pancasila values ??has been carried out by teachers but has not been effective because the learning methods used are not supportive. The conclusion that can be drawn is that using a better method than the lecture method can help teachers implement the values ??of Pancasila.